Aggressive Posterior Retinopathy of Prematurity (APROP): LASER as the Primary Modality of Treatment - Shilpi H Narnaware; Prashant K Bawankule; Dhananjay Raje (Journal of Ophthalmic & Vision Research)
Abstract Purpose: To study the success rate of LASER as a primary modality of treatment in aggressive posterior retinopathy of prematurity (APROP) cases. Methods: This is a prospective case series of 56 eyes of 28 preterm babies (males = 21) with APROP who underwent laser therapy. Babies were divided into groups on the basis of gestational age (GA), birth weight (BW), and postmenstrual age (PMA) at which treatment was performed. GA (in weeks): < 28 (n = 7), 28–30 (n = 11), > 30 (n = 10). BW (in grams): < 1000 (n = 8), 1000–1200 (n = 10), > 1200 (n = 10). PMA (in weeks): < 32 (n = 6), 32–34 (n = 18), > 34 (n = 4). Success was calculated as complete regression of disease without need for any other modality of treatment such as anti-vascular endothelial growth factor (anti-VEGF) or pars plana vitrectomy. Results: The overall success rate was 94.64% (53/56). Two babies who needed additional modality of treatment were < 28 weeks of GA (one eye) and 28–30 weeks (two eyes). One baby (one eye) was < 1000 gm and the other (two eyes) was > 1200 gm, while PMA at which additional treatment was needed was 30 weeks in one baby (one eye) and 33 weeks in the other (two eyes). Conclusion: In this era of anti-VEGF treatment, even in cases of APROP, LASER should still be considered as a primary modality of treatment, as it is a one-time treatment without the concern of systemic side effects and recurrent/persistent avascular zones.